Genetic analysis of SARS-CoV-2 spike gene using Next Generation Sequencing from COVID-19 patients in Erbil/Iraq: NGS and analysis of the S gene in SARS-CoV-2 - Ghareeb, Asma Ameen; Sazan Moffaq Abdulaziz (Cellular and Molecular Biology, 2024)
SARS-CoV-2 has been identified by the WHO as a new virus causing mild to severe respiratory illnesses that belong to the Coronavirus family. The virus underwent rapid and continuous changes in the genetic material, especially the S gene, during COVID-19 pandemic and generated a number of new variants announced by WHO in late 2020. Mutations in the S gene have greatly affected virus pathogenesis as the spike protein is responsible for many critical processes. Delta and Omicron variants were studied extensively due to increased mortality and morbidity rates associated with their pandemic waves. This study aimed to analyse the S gene through NGS in an attempt to identify and characterize the circulating variants among the infected population in Erbil/Iraq. Nasopharyngeal and throat swab samples were collected from hospitalized and non-hospitalized patients with COVID-19 symptoms in Erbil City/Iraq from the 1st of November 2021 to the 28th of February 2022. Following confirmation of SARS-CoV-2 infection by RT-PCR, 15 samples were selected and sent to Intergen Lab (Ankara/Turkey) for NGS and analysis. Following analysis and alignment of the received sequences with the Wuhan-Hu-1 strain (wild-type), Delta variant was identified in 13 samples, and Omicron in two. On the whole, different mutation classes have been observed including nonsynonymous, synonymous, non-frameshift deletions and a non-frameshift insertion. The Delta-specific set of mutations, L452R, T478K and P681R, was detected in all Delta isolates. Both Omicron variants appeared to have 35 mutations. D614G variation was conserved in both variants.